2018
DOI: 10.3390/molecules23040922
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in C–H Activation for Materials Science in the Center for Selective C–H Activation

Abstract: Organic electronics is a rapidly growing field driven in large part by the synthesis of π-conjugated molecules and polymers. Traditional aryl cross-coupling reactions such as the Stille and Suzuki have been used extensively in the synthesis of π-conjugated molecules and polymers, but the synthesis of intermediates necessary for traditional cross-couplings can include multiple steps with toxic and hazardous reagents. Direct arylation through C–H bond activation has the potential to reduce the number of steps an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 68 publications
0
28
0
1
Order By: Relevance
“…So far the highest T c reached is 33.1 Kelvin in PAH superconductors, which was obtained in K-doped 1,2;8,9dibenzopentacene 8 . However, previous theoretical studies showed that PAH superconductors usually exhibit the antiferromagnetic (AFM) ground state [10][11][12][13] and exist the strong electronic correlation effects [13][14][15][16][17][18] , indicating the superconducting mechanism is complicated in aromatic hydrocarbons. Our theoretical predictions have argued that electronic correlations 9 or pressure 19 could enhance high T c in aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…So far the highest T c reached is 33.1 Kelvin in PAH superconductors, which was obtained in K-doped 1,2;8,9dibenzopentacene 8 . However, previous theoretical studies showed that PAH superconductors usually exhibit the antiferromagnetic (AFM) ground state [10][11][12][13] and exist the strong electronic correlation effects [13][14][15][16][17][18] , indicating the superconducting mechanism is complicated in aromatic hydrocarbons. Our theoretical predictions have argued that electronic correlations 9 or pressure 19 could enhance high T c in aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Only electron-phonon coupling is not enough to produce such high-T c superconductivity in alkali metal doped fullerides [13] and PAHs [15]. Meanwhile, the low dimensional feature of organic molecule was proposed to favor the strong electronic correlation effects in these materials such as doped fullerides [16] and PAHs [17][18][19]. While pressure can greatly enhance superconductivity in PAHs such as potassium-doped phenanthrene [20] and picene [21], the realization of superconductivity solely by applying pressure on pristine organic compounds has not been achieved yet.…”
mentioning
confidence: 99%
“…The probe was used in human lung adenocarcinoma cells (A549) for the fluorescent imaging of endogenous and exogenous cysteine. The cells were divided to five groups, and a thiol-blocking reagent N-ethylmaleimide [39] (NEM, 1 mM) was incubated with each group of cells, except the control group, before PÀ Cy (5 μM) was loaded. As shown in Figure 4a, prominent fluorescence was shown in control group cells, which was only incubated with PÀ Cy, indicating that PÀ Cy could successfully sense the endogenous cysteine level in the cell.…”
Section: Resultsmentioning
confidence: 99%